2013
DOI: 10.1155/2013/857047
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcomes of Exercise in Pregnant Women with Chronic Hypertension and/or Previous Preeclampsia: A Randomized Controlled Trial

Abstract: Objectives. To evaluate the association between physical exercise supervised in pregnant women with chronic hypertension and/or previous preeclampsia and maternal and neonatal outcomes. Method. Randomized controlled trial, which included 116 pregnant women with chronic hypertension and/or previous preeclampsia, considered risk of preeclampsia development. They were divided into two groups: study group that performed physical exercise with a stationary bicycle once a week, for 30 minutes; the intensity was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 45 publications
2
35
0
9
Order By: Relevance
“…This study found aerobic and stretching as the predominant physical exercise types in pregnancy and postpartum. This study corroborates previous findings that have found aerobic and stretching exercises as simple, easy to do and adequate in pregnancy (4,(36)(37)(38)(39). Although, cycling and swimming have quantity of support in literature as ideal exercises in pregnancy and postpartum, they were scarcely practiced among the women in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This study found aerobic and stretching as the predominant physical exercise types in pregnancy and postpartum. This study corroborates previous findings that have found aerobic and stretching exercises as simple, easy to do and adequate in pregnancy (4,(36)(37)(38)(39). Although, cycling and swimming have quantity of support in literature as ideal exercises in pregnancy and postpartum, they were scarcely practiced among the women in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Gestantes com hipertensão arterial crônica controlada ou com antecedente pré-eclâmpsia que realizaram mais de dez sessões de exercício em bicicleta estacionária durante a gestação, quando comparadas a um grupo controle, apresentaram melhores resultados perinatais. O grupo de estudo apresentou menor taxa de internação materna na UTI, maior taxa de RN com peso ≥2.500 g, menor taxa de prematuridade e menor taxa de morbidade neonatal 26 . Outro estudo avaliou os efeitos agudos da atividade física aeróbica sobre a pressão arterial, a frequência cardíaca (FC) e o fluxo sanguíneo feto-placentário em gestantes hipertensas que foram submetidas a 30 minutos de exercí-cios em esteira ergométrica a 70% da FC máxima, não se observando alteração do fluxo sanguíneo feto-placentário, mas com aumento da FC e da pressão arterial sistólica na posição sentada 27 .…”
Section: Hipertensão Crônicaunclassified
“…Vários estudos são coincidentes em afirmar que exercício realizado em intensidade leve a moderada não se associa a resultados maternos e fetais adversos 10,11,18,26 . A intensidade do exercício deve ser medida preferencialmente pela FC ou pela sensação subjetiva de esforço (Escala de Borg) 35 .…”
Section: Intensidade Dos Exercíciosunclassified
“…It should be noted that the women in the study were sedentary and therefore had no previous physical conditioning. Another study, which included pregnant women with hypertension and/ or previous preeclampsia, showed similar results, namely no increased risk of adverse maternal and neonatal outcomes, notably hypertensive complications, preterm birth, and low birth weight among women who had exercised during pregnancy 27 . In addition, a, systematic review indicated that physical activity during pregnancy had a protective effect against preeclampsia 28 .…”
Section: Discussionmentioning
confidence: 65%